Treatment patterns in psoriatic arthritis patients newly initiated on oral nonbiologic or biologic disease-modifying antirheumatic drugs - Zhang, Huabin F (BioMed Central, 2014)
INTRODUCTION: This study aimed to describe treatment changes (discontinuation, switching, and therapy add-on) following the initiation of biologic or nonbiologic oral disease-modifying antirheumatic drugs (DMARDs) in psoriatic arthritis (PsA) patients. METHODS: Adult patients with ≥2 PsA diagnoses from physician office visits, initiated on a biologic or nonbiologic oral DMARD, were selected from the Truven Health Analytics MarketScan® Research Database (2005 to 2009). Patients were required to have continuous insurance coverage ≥6 months prior to and ≥12 months post index date (first prescription fill date). Treatment discontinuation, treatment switch, and therapy add-on were captured over the 1 year period following the index date. Treatment changes were described separately for patients initiated on nonbiologic and biologic DMARDs. RESULTS: A total of 1,698 and 3,263 patients were initiated on an oral nonbiologic DMARD and biologic DMARD respectively. For patients initiated on nonbiologic DMARDs, 69% had ≥1 therapy change over the 12 month study period (median time 85 days). Among patients who had a therapy change, 83% discontinued, 29% switched therapy (64% switched to a biologic DMARD), and 25% had a therapy add-on (76% added-on with a biologic DMARD). For patients initiated on a biologic DMARD, 46% had ≥1 therapy change (median time 110 days). Among patients who had a therapy change, 100% discontinued, 25% switched therapy (92% switched to another biologic DMARD), and 7% had a therapy add-on with a nonbiologic DMARD. CONCLUSION: This study suggests that PsA patients newly initiated on a nonbiologic/biologic DMARD do not remain on the index treatment for a long period of time. A better understanding of factors related to these early treatment changes in PsA patients is needed.